Meta-heurísticas GRASP e ILS aplicadas ao problema da variabilidade do tempo de resposta - Menezes, Wesley Willame Dias (2015)
With the advent of technological advances, increasingly demand solutions that use fewer resources, are faster and low cost. As a result, this paper proposed a hybrid approach using metaheuristics Greedy Randomized Adaptive Search Procedure (GRASP) and Iterated Local Search (ILS) applied to the Response Time Variability Problem (RTVP). Since this problem may involve allocation of scarce resources, such as industrial machinery or meeting rooms, going for scheduling of banking customers that require certain conditions, planning of TV ads or route taken by vehicles of logistic companies, etc. For application of the procedure, the movements of shifting symbols, swapping positions between symbols and one called double bridge, which is a mix of movements of shifting and swapping involving opposite symbols were used. The neighborhood structures were based on the movements described above, varying the number of symbols involved. Thus, the results obtained demonstrate that such procedures satisfied the problem and brought consistent results when compared with the literature.